The construction of a photoabsorption spectrum using the FEFF 9 package: a detailed procedure - Rivas Valles, Gildardo (2021)
A procedure to obtain a photoabsorption spectrum assembled from first-principles calculations made with the FEFF 9 spectroscopy package is presented. The calculation consists of obtaining the absorption cross-section of electromagnetic radiation for each electronic shell of an atom inside a solid; the total value is obtained by the sum of the contributions of all shells. A complete spectrum is shown for metallic copper as an example, covering values from ultraviolet above 10 eV (approximately) to x-rays. The spectrum is compared selectively with values from frequently used tables and with results taken from the literature. The advantages of the FEFF 9 package and its limitations are compared; as well, the preliminary nature of the presented results and the need for convergence studies are highlighted, suggesting future work.